Criteria for the presence of films at the boundary of phase separation electrode / electrolyte - Іванов, С. В. (Proceedings of National Aviation University, 2002)
The complex of electrochemical characteristics, which are registered under the condition of formation on the boundary of the electrode / electrolyte of chemosorbed or phase films of difficult soluble compounds, is considered. It is shown that only simultaneous compliance of the parameters of the electrochemical process with several of the established criteria may, with sufficient degree of validity, testify to the formation of film on the electrode when it is studied indirectly by methods.